Pendampingan Optimalisasi Peran Orang Tua untuk Siswa Disabilitas dengan Media Pembelajaran Google Site - Nanik Ulfa; Syahminan Syahminan; Nurul lail Rosyidatul Mu'ammaroh (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
ABSTRACT Education is an intentional activity and process that has begun to be recognized as a necessity by the wider community. According to the law, education is the right of every citizen, including citizens with disabilities. In the government regulations regarding the admission of new students, it is also stated that every school is required to accept students with disabilities. The government regulation has indeed been implemented by the education department with the establishment of inclusive schools; however, the understanding of the implementation of inclusive education is still not comprehensive. The main issue in the implementation of inclusive education is the lack of human resources and parental awareness regarding the support for children with disabilities. This community service activity aims to assist schools and parents with children with special needs so that they can provide optimal services to those special needs students. services can be provided by offering integrated support between schools and families, with the use of media. The community service activities were carried out through stages of socialization, training, technology implementation, evaluation, and program sustainability. The results of these community service activities show an increase in teachers' knowledge of learning instruments, an increase in parental support for children with special needs, and the sustainability of the program with an improvement in the quality of learning in inclusive schools, especially for students with special needs.